Der geschlechtsspezifische Zugriff auf Lesestrategien - Ergebnisse einer Untersuchung im Rahmen unterrichtsdidaktischer Forschung - Grütz, Doris (Linguistik Online, 2025)
Do girls read differently from boys? This contribution presents a study on the empirical research in classroom teaching following an overview on the findings from research on reading which concerns above all the motivational and emotional dimensions of reading. A research was carried out on 1450 pupils of the 4th year of primary school to find out which reading strategies normally applied in the classroom lead to a successful text comprehension in girls and which in boys. The pattern of the research is based on the cognitive-psychological, hierarchic model of text understanding according to Dijk/Klintsch (1983), which considers the process of reading comprehension as interactional and constructive. Two important results of the study are that in the case of girls certain types of readers develop, whereas with boys it is above all the silent reading of a text which leads to the best reading results.